The act : the complete limited series [videorecording (DVD)] - Antosca, Nick; Dean, Michelle; King, Joey, 1999-; Arquette, Patricia, 1968-; Sevigny, Chloë (Universal, 2024)
From writers Nick Antosca (Channel Zero) and Michelle Dean comes The Act, based on Dean's 2016 Buzzfeed article "Dee Dee Wanted Her Daughter To Be Sick, Gypsy Wanted Her Mom To Be Murdered" and explores the tragic relationship between young Gypsy Blanchard and her overprotective mother Dee Dee (Patricia Arquette, in her Primetime Emmy winning performance). As Gypsy strives to break free from her mom's controlling influence, she begins to uncover a host of secrets that propel her down a deadly path.